2015
DOI: 10.3762/bjoc.11.136
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular addition reactions of N-alkyl-N-chlorosulfonamides to unsaturated compounds

Abstract: Summary N-Alkyl-N-chlorosulfonamides add to alkenes under copper(I) catalysis. In reactions of styrene derivatives with terminal double bonds the addition products were obtained in excellent yield and high regioselectivity. Lower yields are obtained in addition reactions to non-aromatic alkenes. The reaction most likely proceeds via a redox catalysis and amidyl radicals, a concerted mechanism has been ruled out and a polar mechanism via chloronium ions would lead to the opposite regiochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a recent report describing a directed C–H alkylation method, we demonstrated that an N -radical species derived from the PCET activation of a 2° sulfon­amide could activate distal aliphatic C–H bonds via 1,5-hydrogen atom transfer (HAT). As sulfon­amide-derived radicals are known to undergo olefin addition with high levels of anti-Markovnikov regio­selectivity, we reasoned that this approach might serve as the basis for a new regio­selective hydro­amination method.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report describing a directed C–H alkylation method, we demonstrated that an N -radical species derived from the PCET activation of a 2° sulfon­amide could activate distal aliphatic C–H bonds via 1,5-hydrogen atom transfer (HAT). As sulfon­amide-derived radicals are known to undergo olefin addition with high levels of anti-Markovnikov regio­selectivity, we reasoned that this approach might serve as the basis for a new regio­selective hydro­amination method.…”
Section: Introductionmentioning
confidence: 99%